Technological design alpaca sausage processing high protein content - Salas De La Torre, Norma (2014)
The current research aims to reassess no traditional meats that in sausage shape get to entry in the local market, according to their nutritional qualities, such as low cholesterol and high protein, which shows the alpaca meat against pork, and also revalue mutton. The presence of Gigartina chamissoi (seaweed) in the formulation is important as a source of iodine, complex polysaccharides (fiber) and natural gelling agents which increase its biological value. Gigartina chamissoi besides raise its nutritional value, constitutes a prebiotic product for counter propensities against cancer cells in tissues such as mucous (esophagus, stomach), glandular (breast) and glandularvessels (prostate). To this effect has been developed an experimental design allowing manufacture sausages in more optimal hygienic conditions. The proximal chemical analysis of the finished product (Table 9) showed that Formulation S-2, resulting in a high protein and low fat. The protein level of Segoviana product (per 35 grams portion) is 3.39 g, and the Formulation S-2 (per 35 grams portion) is 5.23 g. The sensory evaluation was performed using the Hedonic Scale Test (Table 11) yielded optimal results in terms of texture and flavor compared to San Fernando and Segovia brands.